2017
DOI: 10.1016/j.clinph.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Guiding transcranial brain stimulation by EEG/MEG to interact with ongoing brain activity and associated functions: A position paper

Abstract: Non-invasive transcranial brain stimulation (NTBS) techniques have a wide range of applications but also suffer from a number of limitations mainly related to poor specificity of intervention and variable effect size. These limitations motivated recent efforts to focus on the temporal dimension of NTBS with respect to the ongoing brain activity. Temporal patterns of ongoing neuronal activity, in particular brain oscillations and their fluctuations, can be traced with electro- or magnetoencephalography (EEG/MEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
202
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 231 publications
(210 citation statements)
references
References 166 publications
(242 reference statements)
3
202
0
5
Order By: Relevance
“…Future studies need to take potential muscle confounds into account, but might investigate the potential of prefrontal gamma activity as a marker of ongoing pain for the diagnosis and treatment of chronic pain (Davis et al, 2017), especially in the context of neurofeedback and neurostimulation treatment approaches (Jensen et al, 2014;Sitaram et al, 2017;Thut et al, 2017). Thus, they reveal a potential neurophysiological marker of ongoing pain, which could be measured relatively easily using EEG as a noninvasive and broadly available clinical tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies need to take potential muscle confounds into account, but might investigate the potential of prefrontal gamma activity as a marker of ongoing pain for the diagnosis and treatment of chronic pain (Davis et al, 2017), especially in the context of neurofeedback and neurostimulation treatment approaches (Jensen et al, 2014;Sitaram et al, 2017;Thut et al, 2017). Thus, they reveal a potential neurophysiological marker of ongoing pain, which could be measured relatively easily using EEG as a noninvasive and broadly available clinical tool.…”
Section: Discussionmentioning
confidence: 99%
“…Such brain markers of ongoing pain intensity are of particular interest as they constitute potential targets for pain treatment using approaches such as neurofeedback and neurostimulation (Jensen, Day, & Miro, 2014;Sitaram et al, 2017;Thut et al, 2017). Such brain markers of ongoing pain intensity are of particular interest as they constitute potential targets for pain treatment using approaches such as neurofeedback and neurostimulation (Jensen, Day, & Miro, 2014;Sitaram et al, 2017;Thut et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated an immediate behavioral effect, in addition to functional changes as revealed by concurrent MEG/EEG, caused by stimulation frequencies that match those of endogenously generated brain rhythms (see Refs. and ). Using otTCS/tACS, such effects have been reported in multiple cognitive domains such as memory/cognition (e.g., Refs.…”
Section: Frequency‐tuned Transcranial Brain Stimulationmentioning
confidence: 96%
“…However, as mentioned above, the results from HD‐tACS (or dual‐site tACS) studies need to be replicated with validated electrode montages to control the spatiotemporal properties of the stimulation (see Refs. and ). Notably, in a recent study, Kleinert et al .…”
Section: Impact Of Theta Stimulation On Working Memorymentioning
confidence: 96%
See 1 more Smart Citation